The Future of Research on Evidence-based Developmental Violence Prevention in Europe – Introduction to the Focus Section - Eisner, Manuel (International journal of conflict and violence, 2012)
Across Europe, there is an increasing demand for good evidence that can inform policies aimed at reducing violence against and among children and adolescents. However, there is still a paucity of high-quality research on effective prevention of bullying and violence, and researchers from different parts of Europe rarely discuss their findings. The focus section of this issue of the International Journal of Conflict and Violence brings together work by prominent prevention scholars from across Europe, who show that significant progress is being made. The introduction presents nine recommendations about how prevention research could be further strengthened in Europe